Well-being effects of a major negative externality: The case of Fukushima - Katrin Rehdanz; Heinz Welsch; Daiju Narita; Toshihiro Okubo (Kiel Institute for the World Economy (IfW), 2013)
Following a major earthquake off the Pacific coast of Japan, a tsunami disabled the power supply and cooling of three reactors in Fukushima, causing a major nuclear accident on 11 March 2011. Based on a quasi-experimental difference-in-differences approach we use panel data for 5,979 individuals interviewed in Japan before and after the accident to analyze the effect of the accident on people's subjective well-being. Our main hypotheses are that this effect declines with distance to the place of the event but also with distance to other nuclear power plants. To test these hypotheses, we use Geographical Information Systems to merge the well-being data with information on respondents' distance to the Fukushima nuclear plant and on their proximity to nuclear power stations in general. Our empirical results suggest the existence of significant well-being effects of the combined event of the earthquake, tsunami and nuclear accident that are proportional to proximity to the Fukushima site being equivalent to up to 72 percent of annual household income. We find no evidence for increased nation-wide worry about the presence of nuclear power plants near people's place of residence.
Keywords: D62; Q51; Q54; I31; 330; Fukushima; subjective well-being; nuclear disaster; difference-in-differences; willingness to pay